Noradrenergic Modulation of the Piriform Cortex: A Possible Avenue for Understanding Pre-Clinical Alzheimer’s Disease Pathogenesis - Rajani, Vishaal; Yuan, Qi (Frontiers in Cellular Neuroscience, 2022)
Olfactory dysfunction is one of the biomarkers for Alzheimer’s disease (AD) diagnosis and progression. Deficits with odor identification and discrimination are common symptoms of pre-clinical AD, preceding severe memory disorder observed in advanced stages. As a result, understanding mechanisms of olfactory impairment is a major focus in both human studies and animal models of AD. Pretangle tau, a precursor to tau tangles, is first observed in the locus coeruleus (LC). In a recent animal model, LC pretangle tau leads to LC fiber degeneration in the piriform cortex (PC), a cortical area associated with olfactory dysfunction in both human AD and rodent models. Here, we review the role of LC-sourced NE in modulation of PC activity and suggest mechanisms by which pretangle tau-mediated LC dysfunction may impact olfactory processing in preclinical stage of AD. Understanding mechanisms of early olfactory impairment in AD may provide a critical window for detection and intervention of disease progression.